'Blind' to the obvious: Wittgenstein and Köhler on the obvious and the hidden. (October 2014) - Dinishak, Janette
The philosopher Ludwig Wittgenstein cites the Gestalt psychologist Wolfgang Köhler almost as often as he cites William James in his posthumously published writings on the philosophy of psychology. Yet, few treatments of the Wittgenstein–Köhler relation in the philosophical literature could be called sustained discussions. Moreover, most of them treat Köhler as a mere whipping boy for Wittgenstein, one more opportunity to criticize the practice of psychologists. This article emphasizes how much the two thinkers agreed, and the extent to which some of Wittgenstein's work not only agreed with but also has a logical structure parallel to some of Köhler's text. Both thinkers hold that the theoretician should strive to recognize and resist the impulse to step in and purify, distill, streamline, or exclude phenomena: common, everyday experience for Köhler and common, everyday uses of words for Wittgenstein. They both aim to counteract the tendency to discount and disparage what is ordinary and common.